(untitled) - ROBBY, MOCH (Jurnal Ilmu Manajemen (JIM), 2016)
Abstract : Mcdonalds is a fast food restaurant with a brand value of the most valuable in the world. However, it can not guarantee to have a strong brand image is also a particular country such as Indonesia. This study aims to determine the effect of brand image and perceived quality to purchase decisions of consumers Mcdonalds Plaza Surabaya. Type of research used is quantitative research with conclusive research design. The population in this study is that consumers Mcdonalds Plaza Surabaya aged a minimum of 19 years. Samples taken as many as 105 respondents. The sampling method in this study is nonprobability sampling and the technique used is convenience. The technique of collecting data using questionnaires and then analyzed using multiple linear regression. The results of this study indicate that the independent variables consist of brand image and perceived quality significantly influence purchase decisions at Mcdonald’s Plaza Surabaya. Keywords:brand image, perceived quality, purchase decision.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px;" />